Flowering synchronization in hybrid rice parental lines at different sowing dates - Gaballah, Mahmoud; Hamad, Hassan; Bamagoos, Atif; Alharby, Hesham; Ahmed, Sharif; Ismail, Ismail A.; Sohidul Islam, Md; EL Sabagh, Ayman (MDPI, 2021)
Hybrid seed set on the female line depends primarily on its flowering synchronization with the restorer line (R), therefore, the sowing of male and female lines must be planned properly to achieve this. Field experiments on different sowing dates (May 1st, May 15th, and May 30th) of R lines (Giza 178R, Giza 179R, and Giza 181R) and cytoplasmic male sterile (CMS) lines (IR69625A, IR70368A, IR58025A, K17A, and G46A) were carried out at the farm of Sakha Agricultural Research Station, Kafr El-Sheikh, Egypt during 2019 and 2020 to study the effect of sowing dates on flowering synchronization in hybrid rice. The results indicated that the synchronization of flowering between CMS lines and R lines has highly significant effects on the days to 50% heading, number of leaves, effective accumulated temperature (EAT), plant height, panicle exertion percentage, panicle length, number of fertile panicles, panicle weight, seed set percentage, harvest index and seed yield of hybrid rice. The highest seed yield (1.72 and 1.41 t ha−1, respectively in 2019 and 2020) was recorded from the sowing date May 1st and the hybrid combination of Giza 178R × IR58025A (2.06 and 2.12 t ha−1 in 2019 and 2020, respectively). The grain yield had a significant and highly significant positive correlation with the plant height (cm), panicle exertion percentage, panicle length, number of panicles plant−1, panicle weight, seed set percentage, and harvest index. In Egypt, May 1st is the best time for the synchronization of hybrid rice lines and a combination of Giza 178R × IR58025A may be recommended for better performance.